2003
DOI: 10.1034/j.1398-9995.2003.00076.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of guidelines for seasonal allergic rhinitis: a randomized controlled trial

Abstract: Patients with seasonal allergic rhinitis often present severe symptoms which are not well recognized or controlled by physicians using their own criteria of severity and treatment. Using a simple method for the evaluation of the severity and a simple therapeutic scheme based on International Guidelines, patients with seasonal allergic rhinitis presented a significant improvement by comparison with those receiving a non-standardized treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
127
2
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(140 citation statements)
references
References 39 publications
(38 reference statements)
5
127
2
6
Order By: Relevance
“…Physicians should therefore be wary of these limitations and always integrate recommendations in guidelines with their own clinical judgment, after careful clinical evaluation and assessment of patient and disease factors (15). Even with its limitations, following guidelines has proven to be advantageous in the treatment of allergic rhinitis (16) and asthma (17), strengthening the rationale of implementing them.…”
Section: Evidence-based Medicine and Guidelinesmentioning
confidence: 99%
“…Physicians should therefore be wary of these limitations and always integrate recommendations in guidelines with their own clinical judgment, after careful clinical evaluation and assessment of patient and disease factors (15). Even with its limitations, following guidelines has proven to be advantageous in the treatment of allergic rhinitis (16) and asthma (17), strengthening the rationale of implementing them.…”
Section: Evidence-based Medicine and Guidelinesmentioning
confidence: 99%
“…Moreover, an unknown proportion of intermittent and persistent AR patients treat themselves with OTC medications. Management of AR by PCPs can be improved in clinical trials by adoption of the structured approach inherent in guidelines, 18 but studies are needed to assess the long-term outcome and feasibility of these interventions in everyday clinical practice.…”
Section: Recommendationsmentioning
confidence: 99%
“…www.thepcrj.org 18. Please rank the following factors in order of importance to you, where 1 is the most important to you and 8 is the least important to you Improving patients' overall quality of life Preventing the onset or development of comorbidities of allergic rhinitis (AR) e.g.…”
mentioning
confidence: 99%
“…A number of studies reported substantial improvement in quality both in inpatient [1,11,14,18,21,32,50,53,57,60,62,68,78] and outpatient settings [13,29,37,40,42,46]. Numerous studies, including six RCTs [4,7,38,51,63,71], failed to show any positive effects on quality associated with practice guidelines [5,10,20,25,26,36].…”
Section: Do Practice Guidelines Improve Quality Of Care?mentioning
confidence: 99%
“…Finally, three systematic reviews reported that clinical practice guidelines could improve the efficacy, efficiency, and cost-effectiveness of care; however, the size of effect was variable and generally small [6,27,47]. Studies found greater effect with explicit guidelines [6,13,21,23,50,55], defined as ''systematically developed statements to assist practitioner decisions about appropriate health care for specific clinical circumstances'' [27], although practice guidelines improved both processes and outcomes of care, including cost [14,29,53,62], and the results were greater for performance compared with patient outcomes. Clinician involvement in all aspects of guideline development was vital [5,46,53,73].…”
Section: Do Practice Guidelines Improve Quality Of Care?mentioning
confidence: 99%